Direct evidence for EMIC wave scattering of relativistic electrons in space. Issue 7 (23rd July 2016) - Zhang, X.‐J.; Li, W.; Ma, Q.; Thorne, R. M.; Angelopoulos, V.; Bortnik, J.; Chen, L.; Kletzing, C. A.; Kurth, W. S.; Hospodarsky, G. B.; Baker, D. N.; Reeves, G. D.; et al.
Abstract: Electromagnetic ion cyclotron (EMIC) waves have been proposed to cause efficient losses of highly relativistic (>1 MeV) electrons via gyroresonant interactions. Simultaneous observations of EMIC waves and equatorial electron pitch angle distributions, which can be used to directly quantify the EMIC wave scattering effect, are still very limited, however. In the present study, we evaluate the effect of EMIC waves on pitch angle scattering of ultrarelativistic (>1 MeV) electrons during the main phase of a geomagnetic storm, when intense EMIC wave activity was observed in situ (in the plasma plume region with high plasma density) on both Van Allen Probes. EMIC waves captured by Time History of Events and Macroscale Interactions during Substorms (THEMIS) probes and on the ground across the Canadian Array for Real‐time Investigations of Magnetic Activity (CARISMA) are also used to infer their magnetic local time (MLT) coverage. From the observed EMIC wave spectra and local plasma parameters, we compute wave diffusion rates and model the evolution of electron pitch angle distributions. By comparing model results with local observations of pitch angle distributions, we show direct, quantitative evidence of EMIC wave‐driven relativistic electron losses in the Earth's outer radiation belt. Key Points: Direct, quantitative evidence of EMIC wave‐driven relativistic electron loss in the Earth's outer radiation belt is presented EMIC wave scattering effects are quantified based on the observed EMIC wave spectra and local plasma parameters using quasi‐linear theory Dual‐probe analysis reveals wave‐driven losses without being affected by magnetospheric reconfiguration or satellite movement